Screening of four plants commonly used in ethnoveterinary medicine for antimicrobial, antiprotozoal and anti-oxidant activity - Swan, Gerry E. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2004.